Elementos Lúdicos De Apoyo Para La Rehabilitación De La Comunicación De Pacientes Con Afasia De Broca (2024)
The human being is a species that requires communication, however there are times where this communication is damaged by some anomaly in the areas of the brain that allows communication, this condition being called aphasia. This project proposes an idea, generated from industrial design, to support the recovery of people with aphasia outside the environment of the professional who helps this situation to bring it to the comfort of home in a playful and entertaining way for people.